PERLINDUNGAN HUKUM TERHADAP KAUM MINORITAS MUSLIM ATAS PERLAKUAN DISKRIMINATIF DI UNI EROPA - Sari Ganda Kusuma, Miga; Pasek Diantha, I Made; Budi Arsika, I Made (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 02, Februari 2014)
Muslims as a part of minorities in European Union are potentially being discriminated, that this matter shall caught our attention because each EU member state basically recognize and respect the human rights, and certainly enacting their national law as well regulating the protection against discrimination. The analysis of this writings is based on the implementation of EU laws, protection against discrimination given by each EU government and the possible remedies for discriminated Muslims. In principle, the European Union has been applying certain rule regarding discrimination presented as EU Directive which should be implemented by all EU member states. As a form of human rights protection, EU provides four optional settlements on discrimination through international agencies, regional court, EU body and EU Court and also national courts.
Keywords: Discrimination, Muslim Minorities, European Union Laws